2019
DOI: 10.1155/2019/5345161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Human Herpes Virus Type 8 (HHV-8), Human Immunodeficiency Virus-1 (HIV-1), and Syphilis among Female Sex Workers in Malindi, Kenya

Abstract: The prevalence of Human Herpes Virus type 8 (HHV-8), Human Immunodeficiency virus (HIV), and syphilis is high in Sub-Saharan Africa. Studies on HHV-8 in Kenya are few and data on its coinfection with HIV and syphilis scanty. This cross-sectional study among female sex workers (FSWs) in Malindi, Kenya, aimed to determine the prevalence of HHV-8, HIV, and syphilis mono/coinfections and identify associated risk factors. A total of 268 FSWs consented and were administered a structured questionnaire and screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
7
1
Order By: Relevance
“…In the current study, seroprevalence of HIV infection and T. pallidum among FSWs was 27/360 (7.5%) and 45 (12.5%), respectively. In similar studies that have been conducted in Brazil, Panama, Kenya, and Democratic Republic of Congo [15,16,31,32], the prevalence of T. pallidum was lower than that of the current study. Another study in Brazil revealed the seroprevalence of HIV was almost in agreement with the present study whereas the prevalence of T. pallidum (19.7%) was high [11].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…In the current study, seroprevalence of HIV infection and T. pallidum among FSWs was 27/360 (7.5%) and 45 (12.5%), respectively. In similar studies that have been conducted in Brazil, Panama, Kenya, and Democratic Republic of Congo [15,16,31,32], the prevalence of T. pallidum was lower than that of the current study. Another study in Brazil revealed the seroprevalence of HIV was almost in agreement with the present study whereas the prevalence of T. pallidum (19.7%) was high [11].…”
Section: Discussioncontrasting
confidence: 63%
“…Based on the published articles in different parts of the globe, the prevalence of HIV among FSWs ranges from 0.9% to 73.7% [4,18,19]. The prevalence of HCV, HBV, and T. pallidum was also significant in such kind of population group [13][14][15]. Similarly, a study conducted among FSWs in Rwanda indicated 51.1%, 2.5%, and 1.4% overall prevalence for syphilis, HBV, and HCV, respectively [18].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The highest incidence of the virus is in sub-Saharan Africa with 36 to 60% (24). The majority of the available studies reported the seroprevalence of the virus among high-risk populations, including the men who have sex with men (MSMs) or HIV-positives; however, the incidence of the virus in the healthy population has not been well documented (25)(26)(27). The HHV-8 seroprevalence in healthy populations was reported to be 1.3 to 4.4% in Southeast Asia and the Caribbean (28) and 7.3% in the United States (29).…”
Section: Discussionmentioning
confidence: 99%